Retrieval-Practice for Enhancing Students’ Memory in Learning Vocabulary of Preschool Period - Risa Mufliharsi (Hasanuddin University, 2019)
The purpose of the research is applying retrieval practice for enhancing students’ memory in learning vocabulary of preschool period. The data is collected by the data from PAUD Sakura Swadiri in Jakarta in 2017/2018 academic year in four times from 20 students. The instrument that used is direct vocabulary pretest and post test oraly. It is used to find out the progress of each students. The ages of students started from 3 up to 5 years old. The result showed that retrieval practice is effective for enhancing students’ memory in learning vocabulary of preschool period. In this case, retrieval practice improve students memories.